Flipping the script: reevaluating US Army Arctic doctrine. - Shepard, Gregory M. (Fort Leavenworth, KS : US Army Command and General Staff College, 2022)
Current US Army Arctic doctrine has a gap. It focuses on light infantry and does not adequately address combined arms approaches in either the Arctic or Sub-Arctic (ARSAR) regions. Over time, the narrative associated with the Winter War of 1939-1940 and professional discourse's narrow focus on stunning tactical Finnish victories inhibited comprehensive analysis of Arctic warfare. As a result, US Army Arctic doctrine evolved to emphasize light infantry over combined arms operations, violating the principles of ULO and the forthcoming MDO concepts. US Army Arctic doctrine must be revised and portray Arctic warfare as a combined arms undertaking to dominate the ARSAR land domain.